Mechanical Properties of Faecal Sludge and Its Influence on Moisture Retention - Arun Kumar Rayavellore Suryakumar; Sergio Luis Parra-Angarita; Angélique Léonard; Jonathan Pocock; Santiago Septien (ChemEngineering)
The mechanical properties of faecal sludge (FS) influence its moisture retention characteristics to a greater extent than other properties. A comprehensive fundamental characterisation of the mechanical properties is scarcely discussed in the literature. This research focused on bulk and true densities, porosity, particle size distribution and zeta-potential, extracellular polymeric substances, rheology and dilatancy, microstructure analysis, and compactibility in the context of using the FS as a substitute for soil in land reclamation and bioremediation processes. FSs from different on-site sanitation systems were collected from around Durban, South Africa. The porosity of the FSs varied between 42% and 63%, with the zeta-potential being negative, below 10 mV. Over 95% of the particles were <1000 µm. With its presence in the inner part of the solid particles, tightly bound extra-cellular polymeric substances (TB-EPSs) influenced the stability of the sludge by tightly attaching to the cell walls, with the highest being in the septic tank with the greywater sample. More proteins than carbohydrates also confirmed characterised the anaerobic nature of the sludge. The results of the textural properties using a penetrometer showed that the initial slope of the positive part of the penetration curve was related to the stiffness of the sludge sample and similar to that of sewage sludge. The dynamic oscillatory measurements exhibited a firm gel-like behaviour with a linear viscoelastic behaviour of the sludges due to the change in EPSs because of anaerobicity. The high-TS samples exhibited the role of moisture as a lubricating agent on the motion of solid particles, leading to dilatancy with reduced moisture, where the yield stress was no longer associated with the viscous forces but with the frictional contacts of solid–solid particle interactions. The filtration–compression cell test showed good compactibility, but the presence of unbound moisture even at a high pressure of 300 kPa meant that not all unbound moisture was easily removable. The moisture retention behaviour of FS was influenced by its mechanical properties, and any interventional changes to these properties can result in the release of the bound moisture of FS.